The effect of using technical learning in acquiring and learning parallel skill among students of the College of Physical Education and Sports Sciences - HassoonMashkoor, Shaymaa; Ammar Lifta, Iqbal (International Journal of Psychosocial Rehabilitation, 2020)
The core idea of learning depends on ability, willingness, and the amount of time that the learner needs, as the learner is the focus of the educational process, and developing his abilities, capabilities and potential is the main goal in this process, which requires comprehensive and careful attention to the availability of various educational situations that serve the learning process and the availability of the opportunity to achieve performance The optimum of different mathematical skills that reflect the learner’s ability to understand the parts of the skill or movement and its components. The importance of using those educational methods and scheduling them to serve the educational process, especially with difficult skills to learn (parallel skill), is that organizing the learning process and using scientific methods to invest in these methods is the scientific method that is intended to raise the educational level and achieve the goals of the educational process effectively to serve this skill and accelerate it. In light of the findings of the researchers, the following was concluded: The exercises prepared have a positive effect on developing parallel skill learning for students of the College of Physical Education and Sports Science In light of the conclusions reached by the researchers, the following was recommended: 1- The necessity of using skills exercises to develop the skill performance of other activities.